Google Classroom and Students' Performance in Reading Comprehension in Ondo State, Nigeria - Emmanuel, Isaac Friday (Journal of English Language and Pedagogy (JELPA), 2024)
Reading is significant for learning; however, many Nigerian secondary students struggle. In developed nations, teachers engage their students via different online learning apps to complement classroom instruction and improve this skill. However, the same cannot be said for Nigeria, as no established online learning Apps exist. This study, therefore, investigated the effects of Google Classroom on secondary school students' reading comprehension in Ondo State, Nigeria. A quasi-experimental and descriptive research design was adopted for the study. The study population was eighty Senior Secondary School students who were purposefully selected from two secondary schools in Ondo State. The research instruments were the 2022 English Language WAEC questions and the Students' Attitudes Questionnaire (SAQ) r = 0.85. Two research questions were raised, and two research hypotheses were tested. The study's findings revealed that students taught reading comprehension using Google Classroom performed better (`X̅ = 29.98) than those taught using the conventional method (`X̅ =18.88). Similarly, the study's findings revealed that students held a positive attitude toward using Google Classroom for reading comprehension. On the basis of these findings, among others, the study recommended that English language teachers should explore the affordances of Google Classroom to teach reading. Furthermore, schools should allow the controlled use of phones, while the government should organize training for teachers on how to use Google Classroom effectively.